Approaches to the realization of reproductive function in women with systemic lupus erythematosus and antiphospholipid syndrome - Galina A. Vlasova (IP Berlin A.V., 2021)
Aim. To assess the safety and efficacy of assisted reproductive technology (ART) programs in patients with systemic lupus erythematosus (SLE) with/without comorbid antiphospholipid syndrome (APLS).